Impact of breastfeeding on risk of glucose intolerance in early postpartum after gestational diabetes - Vanlaer, Yana; Minschart, Caro; Vrolijk, Hannah; Van Crombrugge, Paul; Moyson, Carolien; Verhaeghe, Johan; Devlieger, Roland; Vandeginste, Sofie; Verlaenen, Hilde; Vercammen, Chris; Maes, Toon; Dufraimont, Els; et al. (Frontiers in Endocrinology, 2024)
Aims: To determine the impact of breastfeeding on the risk of postpartum glucose intolerance in women with gestational diabetes.Methods: Sub-analysis of two multi-centric prospective cohort studies (BEDIP-N and MELINDA) in 1008 women with gestational diabetes. Data were collected during pregnancy and at a mean of 12 weeks postpartum. Multivariate logistic regression was used to estimate the effect of breastfeeding on glucose intolerance, with adjustment for ethnicity, education, income, professional activity and BMI.Results: Of all participants, 56.3% (567) breastfed exclusively, 10.1% (102) gave mixed milk feeding and 33.6% (339) did not breastfeed. Mean breastfeeding duration was 3.8 ± 2.4 and 3.7 ± 2.1 months in the breastfeeding and mixed milk feeding groups (p=0.496). The rate of glucose intolerance was significantly lower in both the breastfeeding [22.3% (126)] and mixed milk feeding [25.5% ( 26)] groups compared to the no breastfeeding group [29.5% (100)], with an adjusted OR of 0.7 (95% CI 0.5-1.0) for glucose intolerance in the breastfeeding group compared to no breastfeeding group and an adjusted OR of 0.7 (95% CI 0.4-1.2) for the mixed milk feeding group compared to the no breastfeeding group. Postpartum, breastfeeding women had a lower BMI, less often postpartum weight retention, lower fasting triglycerides, less insulin resistance and a higher insulin secretion-sensitivity index-2 than the mixed milk feeding and no breastfeeding group. The mixed milk feeding group was more often from an non-White background, had a lower blood pressure and lower fasting triglycerides compared to the no breastfeeding group.Conclusions: Breastfeeding (exclusive and mixed milk feeding) is associated with less glucose intolerance and a better metabolic profile in early postpartum in women with gestational diabetes.